Sistem Informasi Suhu dan Kelembaban Inkubator Telur Ayam Menggunakan Sensor Dht22 Berbasis Mikrokontroler - Ihsanulfu'ad Suwandi (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2023)
Measurement of temperature and humidity generally uses a tool that can determine the value of two physical quantities of a material or system (thermometer or hygrometer). When it comes to hatchery incubators, success and protection are priorities. The microcontroller is a small computer in the form of a chip, DHT22 temperature and humidity sensor with a range of (-40)-80°C. Formulation of the problem, (1) How to get digital data of hatching incubator room temperature using a microcontroller? (2) How is the application of the system to hatching incubators?. Methods of research, analysis, implementation, and simulation (a) Analysis, the lowest ideal temperature for hatching eggs shows a figure of approximately 38°C and the highest is 38.5–39°C. (b) Implementation, starting with the use of DHT22 giving a temperature signal according to whether or not when the condition of the incandescent lamp as a heater will turn on or off, the display will be displayed on the LCD. (c) Simulation, the first stage is the DHT22 schematic to Arduino, the second stage is the relay schematic to Arduino, the third is I2C LCD to Arduino, the fourth is relay to lights and indicators. Based on the analysis, implementation and simulation, conclusions are drawn (1) Digital data related to temperature from the DHT22 sensor displayed on the LCD can be applied to help monitor the hatching process of chicken eggs using an incubator. (2) Arduino board-based microcontrollers can be applied as controllers related to system flow in chicken egg hatching incubators.